The Role of Destination Image in Increasing Tourists' Return Interest - Larasati, Pipit; Palupi, Nur Wulan Intan; Riesha, Riezky Army (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The goal of this study is to the impact of cultural values and facilities on tourists' intention to revisit the Goa Wareh Sukolilo tourist attraction, with destination image as a mediating variable. The study adopts a quantitative approach, employing a simple random sampling method with a sample of 100 tourists drawn from a total population of 5,564 individuals. Data were collected through questionnaires distributed both online and offline. Data analysis was conducted using path analysis with the aid of SPSS version 25. The findings indicate that cultural values and facilities have a positive and significant effect on the destination image, where the influence of cultural values is more dominant than facilities. Destination image is proven to be a significant intermediary variable in strengthening the relationship between cultural values and facilities with revisit intentions. Overall, these findings highlight the importance of paying attention to cultural values, facilities, and destination image in increasing tourists' intentions to revisit. The implications of this study can be used by managers and the government as a reference in developing sustainable tourism development strategies.